Increasing Science Entrepreneurial Thinking Through the PBEST Model: Integrating Sasambo Local Wisdom in Higher Education - Rahman, Nanang; Haifaturahmah; Imam Sofian; Oktiani Pertiwi (LPPM Undiksha, 2025)
University graduates must have Entrepreneurial skills to adapt to an increasingly competitive job market. However, integrating entrepreneurship education in science learning is still a challenge. The Project-Based Entrepreneurial Science Thinking (PBEST) model, which combines the Project-Based Learning (PjBL) model integrated with Sasambo local wisdom, offers an innovative approach to overcoming this problem. This research aims to evaluate the practicality and effectiveness of the PBEST model in improving students' entrepreneurial science thinking. With a pre-test and post-test experimental design, the practicality test data collection uses a questionnaire, while the effectiveness test uses an entrepreneurial science thinking test. Sampling used a random sampling technique. The practicality test was carried out on 20 students, while the effectiveness test involved 72 students from the University. The research results show that PBEST is very practical and effective in increasing indicators of entrepreneurial science thinking, such as observation, new ideas, innovation, creativity, and values. PBEST offers an innovative approach to science education, connecting entrepreneurship with science through the integration of local culture. The implications show that developing a PBEST (Problem-Based, Entrepreneurship, Science, and Technology) based learning model integrated with Sasambo local wisdom has significant potential in shaping students' science entrepreneurial thinking.